Effect of Vermicompost Chicken, Goat and Cow Manure on Growth Response and Yield of Brassica juncea L. on Ultisols - Anandyawati, Anandyawati; Murcitro, Bambang Gonggo; Herman, Welly; Prameswari, Wuri (BPFP Universitas Bengkulu, 2023)
Improvement of Ultisol soil chemical properties can be done by adding organic matter. In this study, vermicompost was used from various animal wastes (chickens, goats and cows), and the optimal growth parameters and nutrient uptake were observed. Research results showed The chicken manure vermicompost had the maximum available P, the goat manure vermicompost had the highest available K, and cow manure vermicompost had the highest total N value. In terms of pH, goat manure vermicompost had the highest pH and the chicken manure vermicompost had the most excellent C/N ratio. Analysis of variance (Anova) showed that the type and dosage of vermicompost had a significant effect on growth parameters (plant height, number of leaves and stem width) and nutrient uptake of N, P and K